Low loss hollow-core optical fibers conjoining tube lattice and revolver structures - Tawhida Akand; Md. Jahirul Islam; Md. Rejvi Kaysir (Results in Optics, 2020)
Recently, hollow-core fibers having negative curvature of the core-cladding boundary become promising for their inexplicit guiding mechanism and ultra-low loss characteristics. Here, we report a modified fiber design, which accumulates the supremacy of tube lattice and negative curvature structures to attain lower confinement loss (CL) for multi bandwidth applications. Extensive numerical simulations are performed, and a noteworthy CL of 4.47 × 10−05 dB/m for LP01 mode at 0.85 μm wavelength and three conspicuous low-loss transmission bandwidth between 0.6 µm and 2.5 µm are found. The CL of the proposed fiber can also be tailored with important parameters like antiresonance order, core diameter, and ring thickness.